Practicing medicine in the COVID-19 Pandemic - Scerri, Mariella; Grech, Victor E (Research and Humanities in Medical Education, 2021)
Frontline clinicians have become society’s line of defence against a raging pandemic. Their stories reflect the uncertainty faced on a daily basis and are witness to their courageous acts first-hand. While research to understand the virus and curtail the disease is readily available, there is sparse information on the emotional hardship medical practitioners have to face. The aim of this commentary is to provide a better understanding of the experiences of doctors practicing medicine during the COVID-19 pandemic, with the focus on Malta and on Maltese doctors currently working abroad. Messages were solicited from those who wished to share their experiences, and were posted, after the author’s permission, on a COVID-19 website. On content analysis of these messages, four major themes emerged: initial reaction, hospital’s response to the COVID-19 pandemic, the new normal, and personal adjustments. These themes provide rich data on how medical practitioners coped during adversity. It portrays their resilience as they came to terms with a rapidly changing health care system and exemplifies the adjustments they made to fall into a new normal. Indeed, their monumental efforts need to be lauded and their outstanding contributions recognised.